AS PRÁTICAS POLÍTICO-PEDAGÓGICAS DA ECONOMIA SOLIDÁRIA NO MARANHÃO: a atuação do FEESMA. - BARBOSA, Juscilene da Conceição (2017)
In this paper, we analyze pedagogical political intentions of State Forum of Solidarity Economy of Maranhão (FEESMA), focusing on its practices and its speeches. The emergence of this collective agent, which has had more organic visibility since 2006, is constituted by a wide range of alliances that disseminated the idea of solidarity economy as a movement of counterpoint to capitalism and sought to legitimize it as a relevant social "issue" with political and ideological implications to work organization engaging "fair and solidary development", "self-management" and "solidarity" symbols. For this analysis, we reflect on discourses and reference agents who elaborate and disseminate the definitions around the concept and practices of solidarity economy. We review the historical context, starting in the 1980s and 1990s, of cash crisis and its restructuring process, when practices and articulations of solidarity economy begin to become visible. We observed the whole growth and institutionalization of solidarity economy process, since 2000s, at national and local levels, notably under Labor Political Party (PT) management in Federal Government, identifying agents’ actions, speeches and political opportunity structures that are considered in this scenario. Finally, we outline a synthesis of realized analyzes from data obtained with empirical research, discussing political-pedagogical perspectives of solidarity economy under the order of capital. For this study, we combined theoretical apparatus of Popular Education, Sociology of Work and Historical Sociology. Research Group: Scientific Culture and Educational Knowledge Production. Research Line: School Institutions, Knowledge and Practices.